1995
DOI: 10.1002/jmv.1890450108
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C virus‐RNA by polymerase chain reaction in dental surgeries

Abstract: The mean prevalence of anti-hepatitis C virus (HCV) in Italy is 0.87%. It reaches 2% in Campania, Southern Italy. Approximately 50% of community acquired non-A, non-B (NANB) hepatitis cannot be associated with known parenteral exposure. A recent Italian study has shown that the only demonstrable risk factor in 9% of acute C/NANB hepatitis is dental treatment. There are no data on direct contamination by HCV of dental surgeries. Possible environmental contamination by HCV-RNA was investigated in dental surgerie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 5 publications
(1 reference statement)
0
29
0
1
Order By: Relevance
“…[20][21][22][23][24] A similarly common potential risk factor is dental treatment, which, like frequent injections, was associated with anti-HCV status only among those younger than 30. Although most studies have not found dental procedures to be a risk for HCV in Egypt or elsewhere, 9,12,25 there is evidence that they may pose a risk, [26][27][28] and in circumstances of prevalent infection and suboptimal sterile technique, they are a logical target for prevention programs. 16 Invasive medical procedures, previously reported to be associated with HCV infection in Egypt, 29,30 had a small increased odds of HCV infection among those older than 30 but not among the younger participants.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] A similarly common potential risk factor is dental treatment, which, like frequent injections, was associated with anti-HCV status only among those younger than 30. Although most studies have not found dental procedures to be a risk for HCV in Egypt or elsewhere, 9,12,25 there is evidence that they may pose a risk, [26][27][28] and in circumstances of prevalent infection and suboptimal sterile technique, they are a logical target for prevention programs. 16 Invasive medical procedures, previously reported to be associated with HCV infection in Egypt, 29,30 had a small increased odds of HCV infection among those older than 30 but not among the younger participants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that there is extensive HCV contamination of dental surgeries after treatment of anti-HCV positive patients. If sterilization and disinfection techniques are inadequate, there is an increased risk of HCV transmission to exposed individuals [Chen et al, 1995;Piazza et al, 1995]. Some studies found an association between HCV infection and sialadenitis [Haddad et al, 1992;Jorgensen et al, 1996]; however, the correlation between periodontal disease and HCV in saliva is not well established [Maticic et al, 2001].…”
Section: Introductionmentioning
confidence: 98%
“…26 Hospitalisation and medical/dental care were implicated as risk factors for non-drug injecting people. Piazza et al 27 demonstrated dental treatment was the only risk factor in 9 per cent of cases of acute HCV infection. Through the use of the polymerase chain reaction (PCR) assay, the same researchers demonstrated HCV genetic material could be recovered from dental equipment, handpieces, burs and workbenches and extensive contamination of dental surgeries occurred following treatment of HCV-infected patients.…”
Section: Transmission To Patientsmentioning
confidence: 99%